PEMBERDAYAAN MASYARAKAT PESISIR TANJUNG TIRAM DALAM PENDAMPINGAN PENGOLAHAN RUMPUT LAUT MENJADI PRODUK BERNILAI EKONOMIS TINGGI - Fekri, Latifa; Yusnaini, Yusnaini; Adimu, Hasan Eldin; Yasidi, Farid (Program Studi Ilmu Kelautan, FMIPA Universitas Tanjungp, 2025)
The coastal area of Tanjung Tiram has great potential in developing seaweed as one of the leading commodities. However, the utilization of seaweed harvests in this area is still limited to the sale of raw materials, so that the economic added value is not optimal. This community service program aims to improve the skills and capacity of the coastal community of Tanjung Tiram in processing seaweed into products with high economic value, such as agar-agar, seaweed crackers, and face masks. The methods used include training, mentoring, and ongoing monitoring. The results of the program showed an increase in participant skills by 80%, with processed products successfully marketed at the local and regional levels. This program is expected to become a model for sustainable empowerment of coastal communities.